Green synthesis of expanded graphite/layered double hydroxides nanocomposites and their application in adsorption removal of Cr(VI) from aqueous solution. (1st February 2019) - Hu, Zhilin; Cai, Limiao; Liang, Jianming; Guo, Xuetao; Li, Wen; Huang, Zhujian
Abstract: A series of expanded graphite/layered double hydroxides (EG/LDHs) nanocomposites were prepared by a green method combining mechanical chemistry and hydrothermal synthesis, which had the advantages of simplicity, easy for industrial-scale production, no use of organic solvents and no waste water generation. The obtained product showed a regular crystal structure and uniform particle size. It was found that a variety of oxygen-containing functional groups were generated at the edge of the graphite nanosheets and inside the sheets. Batch adsorption experiments of Cr(VI) were carried out and the products after adsorption were analyzed by X-ray photoelectron spectroscopy (XPS) in order to explore the adsorption behavior of the graphite nanosheets and EG/LDHs nanocomposites. The results showed that EG/LDHs nanocomposites can be effectively applied to remove Cr(VI) from aqueous solution by physico-chemical adsorption. The adsorption isotherm of adsorbents obtained under different milling conditions can be well described by the Langmuir model. EG/LDHs nanocomposite, produced by ball milling for 5 h at rotational speed of 900 rpm, displayed the optimal Cr(VI) adsorption performance. The presence of oxygen-containing functional groups was beneficial to Cr(VI) adsorption, and the adsorbents induced reduction of Cr(VI) to Cr(III). The green synthesis of EG/LDHs nanocomposites is low-cost and environmental friendly, which is advantageous for advanced treatment of Cr(VI)-containing wastewater. Graphical abstract: Image 1 Highlights: The nanocomposite was prepared by a green method without producing wastewater. The obtained product has a regular crystal structure and uniform particle size. Composite contains abundant oxygen-containing functional groups and defect sites. The total cost of raw materials and energy consumption is economical.